Characterization and Evaluation of Mechanical Behavior of Epoxy-CNT-Bamboo Matrix Hybrid Composites. (2018) - Thakur, Ashish; Purohit, Rajesh; Rana, R.S.; Bandhu, Din
Abstract: Composite materials are the need of the time. The present era cannot think about the development without developing the new materials with exiciting properties to meet the diverse demand of the industry and society. Though lots of researches and developments are going on in thefield of composite materials to meet the industry's requirements, natural fiber reinforced composites are still untouched. By keeping environmental issue in our minds, natural fiber reinforced composites may be a safer substitute to the traditional materials due to their properties like non-toxic, light weight, in-abrasive, economical, easy to use, recyclability, and biodegradability. The natural fiber reinforced composites give a pleasing effect in terms of several mechanical properties as compared to the synthetic fiber based composites. The present work is an attempt to prepare a new composite material by using Bamboo fiber reinforced in the epoxy resin with varying percentage of CNT and examine the mechanical characteristics of the prepared composite specimens. The composite samples were also anayyzed using Atomic Force Microscoe(AFM) to know the their grain size and grain boundary.